Evaluation of the Efficacy of Rifaximin versus Mebeverine in the Treatment of Diarrhea-Predominant Irritable Bowel Syndrome: Rifaximin versus Mebeverine in the Treatment of Diarrhea-Predominant IBS - Ahmad, Shahan; Zaman, Mamoona; Idrees, Nauman; Gul, Rabia; Aziz, Yasir; Ahmad, Faryal (Pakistan Journal of Health Sciences, 2026)
Diarrhea-predominant irritable bowel syndrome (IBS-D) is a widespread functional gastrointestinal disease characterized by frequent abdominal pain and frequent looseness. Antispasmodics such as Mebeverine have proven effectiveness, whereas microbiota-targeted antibiotics such as Rifaximin could be more advantageous because of the effect on gut dysbiosis. Objectives: To compare the effectiveness of Rifaximin and Mebeverine to treat IBS-D through the treatment of diarrhea-predominant irritable bowel syndrome. Methods: This prospective comparative study was conducted at Khyber Teaching Hospital for six months from 1st January 2024 to 30th June 2024. Rifaximin or Mebeverine had been administered to the patients (n = 50 in each group). The collected data were the demographics, IBS Symptom Severity Score (IBS-SSS) at baseline, three months, and six months, and stool consistency, abdominal pain, bloating, and patient-reported satisfaction. The statistical analysis was performed with independent t-tests and chi-square tests; the p-value ≤ 0.05 was taken as significant. Results: Significantly greater improvements were observed in IBS-SSS in the Rifaximin group during three months (p=0.0002) and six months (p<0.0001) than in the Mebeverine group. Even though the Rifaximin group had better outcomes on categorical outcomes, such as stool normalization and first-line resolution of symptoms, most of them were not statistically significant. Conclusions: Rifaximin produced much improved symptomatic improvement as compared to Mebeverine in patients with IBS-D. The findings substantiate its use as a better treatment option clinically.